Archaeological Survey of Fergana Valley in the Years of Independence - Mirsoatova Sayyora Turgunovna; Ahmadaliyeva Nilufar Rustamovna (Universitas Muhammadiyah Sidoarjo, 2023)
It is known from the historiography of archeology that the material culture monuments of the Fergana Valley have been studied for more than 100 years. Fergana Valley has attracted primitive people since ancient times with its favorable paleo-ecological, climatic conditions, fauna and flora.